ChemInform Abstract: 3‐Indolylphosphines as Ligand for Palladium in Suzuki—Miyaura Coupling Reaction of Chloroarenes: Substituent Effects. Issue 38 (30th August 2013) - Saha, Debajyoti; Ghosh, Raju; Sarkar, Amitabha
Abstract Two new indolylphosphines are successfully applied as ligands in the palladium‐catalyzed Suzuki—Miyaura coupling of boronic acids (II) with chloroarenes (I) or benzyl chlorides (IV).